Search for neutral supersymmetric higgs bosons in multijet events at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We have performed a search for neutral Higgs bosons produced in association with bottom quarks in ppÂ collisions, using 260pb-1 of data collected with the D0 detector in Run II of the Fermilab Tevatron Collider. The cross sections for these processes are enhanced in many extensions of the standard model (SM), such as in its minimal supersymmetric extension at large tanâ□¡Î. The results of our analysis agree with expectations from the SM, and we use our measurements to set upper limits on the production of neutral Higgs bosons in the mass range of 90 to 150 GeV. © 2005 The American Physical Society.